2020
DOI: 10.1088/1755-1315/498/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Peat Soil Using Fly Ash, Bottom Ash and Portland Cement: Soil Improvement and Coal Ash Waste Reduction Approach

Abstract: Peat soil is very compressible, which leads to an excessive settlement. Stabilization of peat soil is the way to improve the engineering properties of peat soil through mixing peat with supplementary cementation materials. Therefore, this study aims to investigate the stabilization of peat soil using fly ash, bottom ash and ordinary Portland cement (OPC) to improve the engineering properties of peat soil. Also to examine the possibility of fly ash and bottom ash waste reduction through using them as a binder o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The moisture content for KBpt is accepted to be between the ranges, according to the prior result. In previous studies on moisture content, different number of moisture content have been found, ranges from 491.16 to 985.3 percent according to [14], 678 percent according to [15], and 546.43 percent according to [16]. The moisture content of the soil and its shear strength are inversely proportional on the authority [17].…”
Section: Moisture Content Testmentioning
confidence: 99%
“…The moisture content for KBpt is accepted to be between the ranges, according to the prior result. In previous studies on moisture content, different number of moisture content have been found, ranges from 491.16 to 985.3 percent according to [14], 678 percent according to [15], and 546.43 percent according to [16]. The moisture content of the soil and its shear strength are inversely proportional on the authority [17].…”
Section: Moisture Content Testmentioning
confidence: 99%
“…Stabilized peat showed an increase in compressive strength, with the 89 % Compressive strength increasing during 14 and 28 days from 27 kPa to 42 kPa. (Hauashdh et al 2020)Nazmi carried out experiments like the Unconfined Compressive Strength, California Bearing Ratio (CBR), and Atterberg's Limit to demonstrate how CBA as a stabilizing agent improves the strength parameters of expansive soil. Additionally, coal bottom ash is utilized in the subgrade to improve roadways.…”
Section: Wollastonite Microfibermentioning
confidence: 99%
“…The major components of coal ash consist of oxides of Si, Fe, Al, and Ca, and residual carbons with bottom and fly ashes containing 185.8 mg/kg and 179.2 mg/kg of REEs, respectively , (USDT, 2016). The following Table 1 shows the major oxides of coal fly ash (Hauashdh et al, 2020) while Figure 4 shows trends in coal ash generation based on statistics data from six energyintensive economies. Table 1.…”
Section: Major Oxides Of Coal Ashmentioning
confidence: 99%